Language Assessment in the Normalizing Society - Oliveira, Diego (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2025)
The aim of this study is to discuss linguistic norms present in the Common European Framework, particularly its criteria for assessing phonetic and phonological features in oral performances. For this purpose, we employed Performance Decision Trees to demonstrate that its operational definition for oral proficiency punishes the presence of foreignness in linguistic performances, even when segmental features of the speech do not affect candidates’ performances in linguistic tasks. As a result, we observed that the Common European Framework progressively penalizes the presence of phonetic and phonological elements associated with other languages spoken by candidates.